THE CONTENT OF THE CONCEPT OF SCIENCE AND ISLAMIC VALUES IN FORMING YOUTH'S WORLD VIEW (Scientific journal of the Fergana State University, 2024)
In this article, scientific research studies various types of systematic objects, from structural objects to self-developing complex systems that are mastered at the current stage of civilization development. Today, the effective use of scientific achievements is gaining priority in social development, the well-being of society and the satisfaction of human needs. Also, special attention is paid to the tasks of forming a high appreciation of science and educating people who respect science in society.